Time of Day of BNT162b2 COVID-19 Immunization Affects Total SARS-CoV-2 Antibody Levels but Not Neutralizing Activity. Issue 5 (October 2022) - Filippatos, Filippos; Tatsi, Elizabeth-Barbara; Efthymiou, Vasiliki; Syriopoulou, Vasiliki; Michos, Athanasios
To examine whether immunization time affects the immune responses elicited by the BNT162b2 COVID-19 vaccine, we investigated the possible association between total SARS-CoV-2 spike protein receptor binding domain (TAbs-RBD) and neutralizing (NAbs-RBD) antibodies with vaccination time. A cohort of 468 healthcare workers (mean age [±SD]: 48 [±13] years), were included in the study. One month after the second dose, healthcare workers who were vaccinated between 1500-2200 h had higher TAbs-RBD compared to 0700-1100 h and 1100-1500 h ( p = 0.006). One month after the third dose, healthcare workers who were vaccinated between 0700-1100 h and 1500-2200 h had significantly higher TAbs-RBD compared to 1100-1500 h ( p = 0.034). However, no association of NAbs-RBD with vaccination time was detected after each of the 3 doses ( p > 0.4). Despite the possible effect of BNT162b2 vaccination time in TAbs-RBD levels, possibly due to rhythmic expression of clock genes, neutralizing activity was not associated with vaccination time and, therefore, further investigation is required.